The influence of training variables on lingual strength and swallowing in adults with and without dysphagia. Issue 2 (31st May 2020) - Abe, Takashi; Viana, Ricardo B.; Wong, Vickie; Bell, Zachary W.; Spitz, Robert W.; Yamada, Yujiro; Thiebaud, Robert S.; Loenneke, Jeremy P.
Abstract: Background: Swallowing disorders (dysphagia) occur in a large proportion of individuals over the age of 60. The improvement of tongue strength by resistance exercise is postulated to be directly related to lingual‐palatal pressure generation and bolus propulsion into the pharynx during swallowing. To the best of our knowledge, however, there is no evidence‐based discussion evaluating the strength training variables of the tongue for improving tongue strength maximally. Methods: To solve this problem, we reviewed the relationships between different resistance training variables (i.e. training period, intensity, duration of muscle contraction, volume, and frequency) and the change in muscle strength in the lingual muscle. Results: Our findings show that tongue strength training may improve anterior and posterior tongue strength in both healthy adults and patients with dysphagia. Anterior and posterior tongue strength gradually increased and did not reach a plateau after at least 8 weeks of training. Data for other variables were insufficient to draw clear conclusions. Available data suggest that a training intensity of 60–100% of maximum tongue strength, a contraction time of 2–3 s, a total number of 90–120 repetitions per day, and a training frequency of three times per week appears to result in an improvement in maximal isometric tongue elevation strength in adults with and without dysphagia. Conclusions: Future studies are warranted to better determine if there are dose–response relationships in tongue strength training in healthy adults and patients with dysphagia.